2009
DOI: 10.1016/j.heares.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial receptive field organization of multisensory neurons and its impact on multisensory interactions

Abstract: Previous work has established that the spatial receptive fields (SRFs) of multisensory neurons in the cerebral cortex are strikingly heterogeneous, and that SRF architecture plays an important deterministic role in sensory responsiveness and multisensory integrative capacities. The initial part of this contribution serves to review these findings detailing the key features of SRF organization in cortical multisensory populations by highlighting work from the cat anterior ectosylvian sulcus (AES). In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…The present observation of selective superadditive interactions of responses to multisensory looming signals during early poststimulus onset periods (73-113 ms) that were moreover positively correlated with behavioral facilitation argues for synergistic interplay in humans between principles of multisensory integration established from single-neuron recordings in animals (Stein and Meredith, 1993). These results, in conjunction with the extant literature, highlight the challenge of directly transposing models of multisensory interactions from single-neuron to populationlevel responses and perception (Krueger et al, 2009;Ohshiro et al, 2011). They likewise suggest that multisensory interactions can facilitate the processing and perception of specific varieties of ethologically significant environmental stimuli; here those signaling potential collisions/dangers.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The present observation of selective superadditive interactions of responses to multisensory looming signals during early poststimulus onset periods (73-113 ms) that were moreover positively correlated with behavioral facilitation argues for synergistic interplay in humans between principles of multisensory integration established from single-neuron recordings in animals (Stein and Meredith, 1993). These results, in conjunction with the extant literature, highlight the challenge of directly transposing models of multisensory interactions from single-neuron to populationlevel responses and perception (Krueger et al, 2009;Ohshiro et al, 2011). They likewise suggest that multisensory interactions can facilitate the processing and perception of specific varieties of ethologically significant environmental stimuli; here those signaling potential collisions/dangers.…”
Section: Discussionmentioning
confidence: 52%
“…Superadditive and subadditive hotspots are not stationary within the neuron's receptive field either in cortical (Carriere et al, 2008) or subcortical ) structures and furthermore are not straightforwardly predicted by unisensory response patterns. These features were further evident when data were analyzed at a population level, such that the percentage of integration was higher (in their population of neurons) along the horizontal meridian than for other positions, even though response profiles were uniformly distributed (Krueger et al, 2009). Regarding potential functional consequences of this organization of responsiveness, Wallace and colleagues postulate that such heterogeneity could be efficient in encoding dynamic/moving stimuli and in generating a "normalized" response profile (at least during multisensory conditions) across the receptive field (Krueger et al, 2009).…”
Section: Synergistic Interplay Between Principles Of Multisensory Intmentioning
confidence: 96%
See 2 more Smart Citations
“…Given that random exposure to audiovisual stimuli precludes establishing relationships between stimuli that should or should not be bound together, and that response depressions generally occur for stimuli encoded as separate events [e.g., auditory and visual stimuli presented from distinct spatial locations and therefore likely belonging to independent sources (Meredith and Stein 1996)], it is possible that the incidence of response depressions would also decrease in the random exposure group due to increased inexperience with statistically meaningful relationships between audiovisual events. Recent studies have also shown that the receptive fields of multisensory SC neurons are heterogeneous (Krueger et al 2009) and that neuronal responsiveness and integrative abilities of the same neuron change with the spatial location being tested within the receptive field. Thus, it would be interesting to present stimuli at different, but controlled, receptive field locations (such as within or outside of "hotspots"; see Fig.…”
mentioning
confidence: 99%